Climate change communication and social learning - Review and strategy development for CCAFS - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (2012)
This working paper offers an overview of current theory and practice on climate change communication and social learning in the global South with a view of informing CCAFS strategy in this area. It presents a theoretical framework for understanding social learning and communication approaches and reviews the current landscape of approaches, tools and decision aids in communicating climate change in the context of development. It reviews the challenges of communicating complex issues and scientific evidence as well as relevant local knowledge and perspectives and explores user needs and perceptions both within the CGIAR family and amongst other stakeholders. It provides some case studies from within the CGIAR network of institutions and highlights key themes and recommendations for adopting a social learning approach to communicating climate change and adaptation.